ICRS virtual convention 2021: Orthoregenerative therapy from basic science to clinical application - Chilan Bou Ghosson Leite; Gergo Merkely; Christian Lattermann; Simon Görtz (Elsevier, 2021)
With novel and minimally invasive therapies increasingly sought after to address acute and chronic conditions of the musculoskeletal system, orthoregenerative strategies have been gaining attention given their potential to modulate and improve the body's healing response. Aiming to facilitate communication, education and translational research on orthobiologics, the International Cartilage Regeneration & Joint Preservation Society Virtual Convention 2021 was conducted to outline key strategies frequently used in research and clinical application, including blood-derivatives, stem cells, biomechanical concepts and engineering strategies, as well as exploring new developments and promising targets in the treatment of musculoskeletal disorders. This article will summarize the International Cartilage Regeneration & Joint Preservation Society Virtual Convention 2021, reviewing both the scientific "Know Why" as well as the clinical "Know How", to encompass the entire spectrum of orthoregeneration, bench to bedside, in 2021 and beyond.